THE IMPLICATION OF PROFITABILITY AS A MODERATING IN THE RELATION OF ENVIRONMENTAL CERTIFICATION AND FINANCIAL PERFORMANCE TO MARKET REACTION - Widiatami, Anna; Khasanah, Nasriatun; Nurkhin, Ahmad; Aeni, Ida (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
This study aims to analyze and empirically evaluate the effect of financial and non-financial information submitted through annual reports on the market reaction, proxied by trading volume activity. A study was conducted in 103 manufacturing companies listed on the Indonesian Stock Exchange for the 2017-2021 period with 515 annual reports. The panel data moderating regression results show that environmental certification and financial performance, measured by Sales growth, market value added, and Tobin's Q Ratio, do not affect the market reaction. However, return on equity as a Profitability measurement can strengthen the relationship between environmental certification and sales growth in trading volume activity. This study implies that a high return on equity in companies attracts an investor more than environmental certification. Besides, it could change the confidence of the investor to invest in a company that has been obtaining ISO 14001 certificates.